Dietary Iron Overload and Hfe−/− Related Hemochromatosis Alter Hepatic Mitochondrial Function - Christine Fischer; Chiara Volani; Timea Komlódi; Markus Seifert; Egon Demetz; Lara Valente de Souza; Kristina Auer; Verena Petzer; Laura von Raffay; Patrizia Moser; Erich Gnaiger; Guenter Weiss (MDPI AG, 2021)
Iron is an essential co-factor for many cellular metabolic processes, and mitochondria are main sites of utilization. Iron accumulation promotes production of reactive oxygen species (ROS) via the catalytic activity of iron species. Herein, we investigated the consequences of dietary and genetic iron overload on mitochondrial function. C57BL/6N wildtype and Hfe−/− mice, the latter a genetic hemochromatosis model, received either normal diet (ND) or high iron diet (HI) for two weeks. Liver mitochondrial respiration was measured using high-resolution respirometry along with analysis of expression of specific proteins and ROS production. HI promoted tissue iron accumulation and slightly affected mitochondrial function in wildtype mice. Hepatic mitochondrial function was impaired in Hfe−/− mice on ND and HI. Compared to wildtype mice, Hfe−/− mice on ND showed increased mitochondrial respiratory capacity. Hfe−/− mice on HI showed very high liver iron levels, decreased mitochondrial respiratory capacity and increased ROS production associated with reduced mitochondrial aconitase activity. Although Hfe−/− resulted in increased mitochondrial iron loading, the concentration of metabolically reactive cytoplasmic iron and mitochondrial density remained unchanged. Our data show multiple effects of dietary and genetic iron loading on mitochondrial function and linked metabolic pathways, providing an explanation for fatigue in iron-overloaded hemochromatosis patients, and suggests iron reduction therapy for improvement of mitochondrial function.